Timing of use of cod liver oil, a vitamin D source, and multiple sclerosis risk: The EnvIMS study. (December 2015) - Cortese, Marianna; Riise, Trond; Bjørnevik, Kjetil; Holmøy, Trygve; Kampman, Margitta T; Magalhaes, Sandra; Pugliatti, Maura; Wolfson, Christina; Myhr, Kjell-Morten
Background: Low vitamin D levels have been associated with an increased risk of multiple sclerosis (MS), although it remains unknown whether this relationship varies by age. Objective: The objective of this paper is to investigate the association between vitamin D3 supplementation through cod liver oil at different postnatal ages and MS risk. Methods: In the Norwegian component of the multinational case-control study Environmental Factors In Multiple Sclerosis (EnvIMS), a total of 953 MS patients with maximum disease duration of 10 years and 1717 controls reported their cod liver oil use from childhood to adulthood. Results: Self-reported supplement use at ages 13–18 was associated with a reduced risk of MS (OR 0.67, 95% CI 0.52–0.86), whereas supplementation during childhood was not found to alter MS risk (OR 1.01, 95% CI 0.81–1.26), each compared to non-use during the respective period. An inverse association was found between MS risk and the dose of cod liver oil during adolescence, suggesting a dose-response relationship ( p trend = 0.001) with the strongest effect for an estimated vitamin D3 intake of 600–800 IU/d (OR 0.46, 95% CI 0.31–0.70). Conclusions: These findings not only support the hypothesis relating to low vitamin D as a risk factor for MS, but further point to adolescence as an important susceptibility period for adult-onset MS.